ANALISA PERBANDINGAN PERFORMANSI SINGLE DAN DOUBLE TURBOCHARGER PADA CUMMINS ENGINE K50 SERIES - Hein Hein; Puji Saksono; Gunawan Gunawan (TRANSMISI, 2016)
Application development engine in the heavy equipment is currently lead to the development of environmentally friendly technologies but with a better performance without changing the size or dimensions of the engine. Performance comparison analysis between Cummins engine applications which use single and double turbocharger to the performance, efficiency and fuel comsumtion required to provide a reference for users of heavy equipment unit (customer). This research was conducted at PT. Altrak Balikpapan branch in 1978 as a distributor of Cummins engines Indonesia. The research object is the Cummins engine type "K50" series with KTA-50 engine models and KTTA-50. Achievement of maximum engine power in the can with the provision of 100% load at 1900 rpm engine speed, which amounted to 1798 HP at KTA-50 and 1993 HP at KTTA-50. The increase in the value of the torque which can be different from the values ??of engine power, because the maximum torque is not in a position rated speed but at 100% load at 1500 rpm engine speed. This position is often referred to as the peak torque and the maximum torque values ??in may of 1487 lb.ft at KTA-50 and 1656 lb.ft at KTTA-50. The result of the calculation is theoretically found also that with the increase in engine power then an increase in fuel consumption linearly. The thermal efficiency of the engine KTTA-50 amounted to 42.29% larger than the engine-50 summit that only 42.23%.